“Frecuencia de anemia en los pacientes adultos mayores de la ciudad de Machala, 2014” - Ajila Vacacela, José Geovanny (2015)
This study was performed in the months of July and August 2014. The objective was to determine the frequency of anemia in adults over the city of Machala, 2014, 388 elderly outpatients were studied, all blood count were performed. Showing a prevalence of anemia of 19.85%. 52% have an age range between 75-90 years, 47% is the age range between 65 and 74 years and 1% of older adults aged> 90 years old presented anemia, 60% of seniors were women and 40% men.